2019
DOI: 10.1111/1756-185x.13735
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Ankylosing Spondylitis Disease Activity Score with C‐reactive protein (ASDAS‐CRP) and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) in patients with axial spondyloarthritis (axSpA) in Singapore

Abstract: Introduction:The Ankylosing Spondylitis Disease Activity Score with C-reactive protein (ASDAS-CRP) and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) are commonly used instruments for measuring disease activity. However, few studies have assessed their psychometric properties in patients with axial spondyloarthritis (axSpA). We aimed to assess the validity and reliability of ASDAS-CRP and BASDAI in patients with axSpA in Singapore. Methods:Cross-sectional data from 280 patients with axSpA from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The correlation coefficients between the BASDAI and ASDAS-CRP/ASDAS-ESR were 0.7203/0.7590 ( p < 0.0001, both), which were consistent with those reported in prior studies ( 7 , 16 18 ). Our data determined the disease activity state cut-offs for BASDAI at 2.1/2.0, 3.1/2.6, and 3.7/4.8 for inactive disease, low disease activity, high disease activity, and very high disease activity, while using ASDAS-CRP/ASCAS-ESR as references.…”
Section: Discussionsupporting
confidence: 90%
“…The correlation coefficients between the BASDAI and ASDAS-CRP/ASDAS-ESR were 0.7203/0.7590 ( p < 0.0001, both), which were consistent with those reported in prior studies ( 7 , 16 18 ). Our data determined the disease activity state cut-offs for BASDAI at 2.1/2.0, 3.1/2.6, and 3.7/4.8 for inactive disease, low disease activity, high disease activity, and very high disease activity, while using ASDAS-CRP/ASCAS-ESR as references.…”
Section: Discussionsupporting
confidence: 90%
“…Patient-reported outcomes included the validated Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), pain score, patient global assessment (PtGA), Health Assessment Questionnaire-Disability Index (HAQ-DI), and the 36-item Short Form Health Survey (SF-36), all of which have been validated in the Asian context for patients with SpA 17,18,19,20,21 . The BASDAI consisted of 5 domains including fatigue, back pain, peripheral joint pain, enthesitis pain, and morning stiffness (severity and duration), collected on a 0-10 NRS, with 10 indicating worse severity; the mean of the 5 domains was scored.…”
Section: Methodsmentioning
confidence: 99%
“…The BASDAI has construct validity in that it is correlated with the Ankylosing Spondylitis Quality of Life Index (ASQoL), the ASAS Health Index (ASAS HI), the Bath Ankylosing Spondylitis Function Index (BASFI), the Bath Ankylosing Spondylitis Global Score (BAS‐G), and others (35–42).…”
Section: Bath Ankylosing Spondylitis Disease Activity Index (Basdai)mentioning
confidence: 99%
“…Four of the items in the ASDAS are taken from the BASDAI, and these items in general have good reliability (19). A single‐center study has shown poor internal consistency (Cronbach’s α = 0.33) (40).…”
Section: Ankylosing Spondylitis Disease Activity Score (Asdas)mentioning
confidence: 99%
See 1 more Smart Citation